Biochemical and structural characterization of enzymes in the 4-hydroxybenzoate catabolic pathway of lignin-degrading white-rot fungi - Eugene Kuatsjah; Alexa Schwartz; Michael Zahn; Konstantinos Tornesakis; Zoe A. Kellermyer; Morgan A. Ingraham; Sean P. Woodworth; Kelsey J. Ramirez; Paul A. Cox; Andrew R. Pickford; Davinia Salvachúa (Cell Reports)
Summary: White-rot fungi (WRF) are the most efficient lignin-degrading organisms in nature. However, their capacity to use lignin-related aromatic compounds, such as 4-hydroxybenzoate, as carbon sources has only been described recently. Previously, the hydroxyquinol pathway was proposed for the bioconversion of these compounds in fungi, but gene- and structure-function relationships of the full enzymatic pathway remain uncharacterized in any single fungal species. Here, we characterize seven enzymes from two WRF, Trametes versicolor and Gelatoporia subvermispora, which constitute a four-enzyme cascade from 4-hydroxybenzoate to β-ketoadipate via the hydroxyquinol pathway. Furthermore, we solve the crystal structure of four of these enzymes and identify mechanistic differences with the closest bacterial and fungal structural homologs. Overall, this research expands our understanding of aromatic catabolism by WRF and establishes an alternative strategy for the conversion of lignin-related compounds to the valuable molecule β-ketoadipate, contributing to the development of biological processes for lignin valorization.